ANALISIS PENERAPAN HEAT TRANSFER PADA PEMANASAN BAHAN BAKAR BENSIN MELALUI PIPA KAPILER BERSIRIP RADIAL DI DALAMUPPER TANK RADIATOR UNTUK MENINGKATKAN PERFORMANSI MESIN KIJANG - Danar Susilo Wijayanto; Ngatou Rohman; Ranto Ranto; Husin Bugis; Arif Nurachman; Febryan Alfianto Nugroho (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2013)
The purpose of this study wereto determine the effect usage of gasoline heating through a capillary tube which is radial finned in the upper tank of radiator on fuel consumption and exhaust emissions of CO and HC in the engine of Toyota Kijang.This study is experimental. The sample in this study was the machine of Toyota Kijang with machine number 7855290. Free variable of the research is the usage of fuel heating with fin variations on the copper capillar tube consist of copper capillar tube without fin, finned copper capillar tube with the ranges between the fins are 10 mm, 20 mm, and 30 mm and variations of engine speed at 1000 r.p.m., 2000 r.p.m., and 3000 r.p.m. Experimental method to measure the fuel consumption is done by recording the time required for spent fuel 50 cc and exhaust emissions of CO and HC in the engine of Toyota Kijang.The result of this research shows that the average consumption at engine speed 1000 r.p.m. on the normal condition Toyota Kijang has average fuel consumption 32,066×10-3 cc per cycle. In the usage of fuel heating using three copper tubes with the range between the fins is 10 mm fuel consumption by 25,174×10-3 cc per cycle. Fuel consumption decreased by 6,892×10-3 cc per cycle or 21,58%. At engine speed 2000 r.p.m. on the normal condition Toyota Kijang average consumption 38,487×10-3 cc per cycle. In the usage of fuel heating using three copper tubes with the range between the fins is 10 mm fuel consumption by 28,121×10-3 cc per cycle. Fuel consumption decreased by 10,366×10-3 cc per cycle or 26,93%. At engine speed 3000 r.p.m. on the normal condition Toyota Kijang average consumption 36,783×10-3 cc per cycle. In the usage of fuel heating using three copper tubes with the range between the fins is 10 mm fuel consumption by 31,187×10-3 cc per cycle. Fuel consumption decreased by 5,596×10-3 per cycle or 15,21%. The conclusion of this research is the usage of fuel heating using three copper tubes with the range between the fins is 10mm in the upper tank of radiator can reduce the biggest lowers fuel consumption on the Engine of Toyota Kijang 1989.This research also shows that: the usage of fuel heating use 3 finned copper tubes in the upper tank of radiator can reduce the highest level on exhaust emissions of CO and HC in the engine of Toyota Kijang. The different of CO exhaust emission is 2,54 % volume or 85 % while the HC exhaust emission is 139,667 ppm volume or 72 %.